P3.397 Prevention Services, Health-Seeking Behaviours, and STI Prevalence Among Female Entertainment Workers in Cambodia. (13th July 2013) - Killam, W P; Mun, P; Mutuc, J D; Chann, N; Chan, S; Shiraishi, R W; Warren, D; Vun, M C
Abstract : Background: Cambodia's brothel-based prevention programmes successfully promoted condom use among female sex workers since 1994. HIV and sexually transmitted infection (STI) prevalence decreased precipitously from 1998 to 2006. In 2008 brothels became illegal, and entertainment venues (karaoke bars, beer gardens and massage parlours) increased rapidly. Many female entertainment workers (FEWs) at these venues provide transactional sex. We explored receipt of prevention services and associated knowledge, health-seeking behaviour, and prevalence of STIs and HIV among Cambodian FEWs. Methods: In 2011, a stratified multi-stage cluster survey was conducted among 2, 564 FEWs in selected provinces of Cambodia. Voluntary, anonymous interviews collected information on receipt of prevention services and sexual behaviours. Biological testing was conducted for HIV, syphilis, gonorrhoea, and chlamydia. Analyses were weighted and controlled for the design of the survey. Logistic regression models were used to examine associations between interventions, health-seeking behaviours, and STIs. Results: Prevalence of any STI and HIV was 20.8% and 2.6%, respectively. Among FEWs, 86.9% reported receiving HIV/STI education, most commonly from an outreach worker (47.7%) or television (46.1%). Receipt of a prevention message was associated with getting an HIV test (odds ratio [OR] = 2.6, 95% confidence interval [CI]: 1.8–3.6) and sexual health check-up (OR = 2.6, 95% CI: 1.7–3.9) in the last 12 months, and higher HIV knowledge (OR = 1.7, 95% CI: 1.1–2.8). Condom provision was also associated with health-seeking behaviours. Receipt of prevention interventions was not associated with reported recent condom usage or STIs, although further analyses are ongoing in order to adjust for potential confounders. Conclusion: The rapid expansion of non-brothel-based entertainment work challenges prevention efforts among Cambodian FEW, who have high STI prevalence and risk behaviours. Prevention education and condom provision are associated with increased knowledge and health seeking behaviours, but not self-reported condom use or reduced STI prevalence in this cross-sectional snapshot.